História da formação do pensamento geográfico cearense: entre o saber, o conhecimento científico e a docência (1887-1947) - Mendes, Eluziane Gonzaga (2012)
Analyze the contribution of Historical Geographic Anthropological Institute, and its intellectuals in the construction of cearense Geography, understanding its influence to the formation of this knowledge as knowing: educational, scientific and academic was the main aim of the thesis. The time scale was given starting from 1887, date of implementation of the Institute of Ceará until the decade of 1947, with the foundation of Geographic college degree, Philosophy Catholic College of Ceará, responsible for teacher’s formation to secondary education. Other institutions were fundamental for teacher’s formation to Geography, such as Liceu of Ceará, Escola Normal and Prainha Seminar, besides private and public schools, which contributed to the constitution of a basic curriculum to this subject. The creation period of the Ceará Institute occurred when in Brazil lived up effervescence of cultural, scientific and literary institutions creation. Fortaleza city and the institute intellectuals took part of this context. We identified, by reading trajectory of these scholars, those who were prominent in scientific and educational written Geography, thus it is highlighted: The Pompeu family, among the several naturalists and researchers of that period. We made use of historiographical methodology with the collection and analysis of primary and secondary sources, as: digital and printed documents, manuscripts, requests, rare books and the Institute of Ceará Magazines - RIC, the latter considered the main source and the contribution for formation and systematization of the cearense geographic knowledge. Several findings could be retreated with the thesis development, among these, understand that although the cearense Geography, between the end of the century XIX and mid-century XX, being linked to the thought of the great centers, following trends of geographic Positivism, Determinism and Possibilism, coming from France and Germany, already presented among the local scientific institutions the formation of endogenous knowledge, broadcast through scientific magazines and through textbooks. In this sense, the analysis of rare books of school geography, revealed the existence of the same line of thinking and writing between scientific knowledge produced at the time and the knowledge taken into schools. It was also revealed, in the research, the search of the scholars when proving assumptions, which could support, theoretically, the origin and identity of Ceará, cultivating the intention of writing the “official” history and geography. It was verified that the school geography assumed functions linked to the historical reality of the country, as the formation of nationality, taken into schools through books and speeches of the teachers. It was knowledge transposed of the science world to school, and despite the contingent and popularization scientific knowledge by didactic materials, until the mid-fifties, the geography teaching was based on memorization of concepts and designations. The teachers trained in this period kept reproducing in school institutions the principles of a traditional and classical education. Ultimately, we understand that weave the trajectory of Geography of Ceará was an opportunity of unveiling this science, of its scientific importance in the local education history and in formation of Brazilian Geography.